Romania : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2015)
The paper discusses recommendations made in a fiscal transparency evaluation report for Romania. Seven recommendations are made to improve the level of information available to decision makers and the public. The report recommends reducing fragmentation of existing fiscal reporting and expanding the institutional coverage to include the wider public sector. It also recommends improving the timeliness, quality, and integrity of fiscal reports and financial statements through publishing reconciliations between cash and accrual based reports and enforcing strict timelines for publication of financial statements.